Strengthening Paradiplomacy between West Kalimantan and Malaysia through the Socio-Economic Working Group Program: A Case Study on the Protection of Indonesian Migrant Workers during the COVID-19 Pandemic - Manda Retha Cahyaningrum; Eva Nur Aprillia (Universitas Muhammadiyah Yogyakarta, 2024)
The World Health Organization’s (WHO) designation of COVID-19 as a pandemic in mid-March 2020 demanded adaptive policies across various sectors, including the protection of Indonesian Migrant Workers (PMI) abroad. This study examines how paradiplomacy carried out by the West Kalimantan Provincial Government contributes to mitigating the negative impact of the pandemic on PMI in Malaysia, particularly through the framework of the Malaysian-Indonesian Socio-Economic Working Group (KK SOSEK MALINDO). Many countries, including Malaysia, implemented social distancing and lockdown measures to curb the spread of COVID-19, which also led to economic slowdowns affecting migrant workers. Given the large number of Indonesian migrant workers in Malaysia (over 80,000), safeguarding their rights became a key concern. The findings of this research reveal that the paradiplomacy approach, which facilitates collaboration among local governments and other relevant stakeholders, has helped address challenges faced by PMI—such as issues of legal status, healthcare access, and the provision of social assistance. This study advances our understanding of paradiplomacy in the Indonesia-Malaysia border region and underscores the importance of cross-actor synergy in the context of responding to global crises.